Design, fabrication, and characterization of multistable mechanical metamaterials for trapping energy. (April 2019) - Tan, Xiaojun; Chen, Shuai; Wang, Bing; Zhu, Shaowei; Wu, Linzhi; Sun, Yuguo
Abstract: In this study, a novel multistable mechanical metamaterial, composed of multiple magnets systems, was presented. Several configurational models of magnets system were proposed. Using theoretical and experimental methods, the energy storage performance of the metamaterial was optimized, the parameters affecting the energy storage performance were discussed and the optimum solution was given. The energy trapping mechanism of this metamaterial was introduced. The specimen of the material was fabricated by combination of Fused Deposition Modeling (FDM) technology and interlock method. The quasi-static uniaxial compression was used to study the energy trapping ability of the metamaterial. The impact experiments were also conducted to test the cushion performance of the metamaterials. Experimental results show that the presented metamaterial exhibits good property, like thresholding the acceleration and completely reusable, in the application of impact protection. Moreover, one special behavior, earlier transformation, was firstly found in this study, and the mechanism was introduced.